2020
DOI: 10.1080/03601277.2020.1856956
|View full text |Cite
|
Sign up to set email alerts
|

Process and outcomes of telephone reassurance program training for older adult volunteers

Abstract: The purpose of this study was to examine the experience of Senior Companions with telephone reassurance program training delivered via Zoom and the feasibility of using teleconferencing as a platform for training older adult volunteers during the COVID-19 pandemic. Volunteers were recruited from a local Senior Companion Program. We assessed training enrollment and participation rates. We also examined the overall participant experience with the program training by asking structured/semi-structured questions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Two articles described telephone outreach programs in which staff or volunteers conduct check-ins with isolated older adults. One article was a process evaluation of a virtual training program for older adult volunteers in a telephone outreach program (Lee, Fields, Cassidy, & Feinhals, 2021), while the other article reported on a telephone outreach program established by the Health Black Elders Centre for their members (Rorai & Perry, 2020). Anecdotally it was reported that older adults viewed the calls positively and some were able to be referred/connected to needed services.…”
Section: Effects Of Social Isolation and Loneliness On Older Adults D...mentioning
confidence: 99%
“…Two articles described telephone outreach programs in which staff or volunteers conduct check-ins with isolated older adults. One article was a process evaluation of a virtual training program for older adult volunteers in a telephone outreach program (Lee, Fields, Cassidy, & Feinhals, 2021), while the other article reported on a telephone outreach program established by the Health Black Elders Centre for their members (Rorai & Perry, 2020). Anecdotally it was reported that older adults viewed the calls positively and some were able to be referred/connected to needed services.…”
Section: Effects Of Social Isolation and Loneliness On Older Adults D...mentioning
confidence: 99%
“…To prepare volunteers for their role as Caring Callers, training via Zoom was required one month prior to placing their first phone call. The training manual was divided into three parts: (1) the program overview; (2) understanding the needs of socially isolated older adults; and (3) processes and procedures of the program (Lee et al, 2021a).…”
Section: Methodsmentioning
confidence: 99%
“…Volunteers did not follow a script and each call was composed of “(1) basic safety checkups, (2) events of the week and the clients’ reactions to the events, (3) topics raised by the clients, and (4) discussion of coping methods” (Lee et al, 2021b: p. 5). Volunteers were provided a list of existing community resources that may adequately address some common issues (e.g., food assistance or transportation) reported by their clients (see Lee et al, 2021a for an overview of the Caring Callers training).…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the pandemic and after, concerns have been raised about the potential adverse impact on older adults in terms of both their physical and emotional health as social distancing measures were put in place, and meaningful activities, such as volunteerism, were paused or suspended (Berg-Weger and Morley, 2020;Grotz et al, 2020;Wolman et al, 2022). Despite the disruptions, uncertainty and health risks, some older adults volunteered throughout the Covid-19 pandemic (Addario et al, 2022;Chan et al, 2021;Dury et al, 2023;Lee et al, 2021; (Information about the authors can be found at the end of this article.) Mak and Fancourt, 2022;Principi et al, 2022).…”
mentioning
confidence: 99%